Nasihat Guru Kepada Murid dalam Kitab Washoya Al Aba Lil Abna Karya Syekh Muhammad Syakir dan Korelasinya Terhadap Nasihat Orang Tua Betawi - Irfan, Ahmad; Ayuhan, Ayuhan; Setiady, Dicky (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2026)
The decline in students’ moral conduct toward teachers and parents has become a critical issue in contemporary Islamic education, necessitating a re-examination of ethical sources that shape teacher–student and parent–child relationships. This study employs a library research method by analyzing Washoya Al Aba Lil Abna by Muhammad Syakir and Betawi parental advice through a descriptive-analytical approach. The findings reveal a strong continuity of values between the two sources, particularly regarding four key principles: the equal moral status of teachers and parents as authoritative figures, the importance of seeking the riḍā (approval) of teachers and parents, the obligation to adorn knowledge with noble character, and the encouragement of self-improvement through personal effort rather than reliance on the prestige of teachers or family lineage. These findings affirm that Betawi parental advice reflects ethical values aligned with the teachings of Sheikh Muhammad Syakir and remains relevant for reinforcing students’ foundations of adab in the contemporary era. This study contributes to the development of an Islamic education model grounded in local wisdom, making Islamic education more closely connected to students’ everyday lives.